Job Protection Deregulation in Good and Bad Times - Duval, Romain (IMF Working Papers; Working Paper, 2017)
This paper explores the short-term employment effect of deregulating job protection for regular workers and how it varies with prevailing business cycle conditions. We apply a local projection method to a newly constructed 'narrative' dataset of major regular job protection reforms covering 26 advanced economies over the past four decades. The analysis relies on country-sector-level data, using as an identifying assumption the fact that stringent dismissal regulations are more binding in sectors that are characterized by a higher 'natural' propensity to regularly adjust their workforce. We find that the responses of sectoral employment to large job protection deregulation shocks depend crucially on the state of the economy at the time of reform--they are positive in an expansion, but become negative in a recession. These findings are consistent with theory, and are robust to a broad range of robustness checks including an Instrumental Variable approach using political economy drivers of reforms as instruments. Our results provide a case for undertaking job protection reform in good times, or for designing it in ways that enhance its short-term impact.